ARAHAN PENGELOLAAN DAERAH ALIRAN SUNGAI BERDASARKAN INDEKS BAHAYA EROSI (IBE) SUB DAS PITU RIASE KABUPATEN SIDRAP - Andi Nurhawaidah; Amir Tjoneng; Iskandar Hasan (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2019)
The purpose of this study is 1)Analyzing the level of erosion that occurs in various land uses in the Pitu Riase sub-watershed, Sidrap Regency. 2)Assess tolerable erosion rates (TSL). 3)Analyze the erosion hazard index (EHI).4)Determine recommendations for land use in the Pitu Riase sub-watershed in Sidrap Regency. This research was carried out in the Pitu Riase Sub-watershed, Sidenreng Rappang Regency from February to April 2018. As technology developed, there were several general methods that could be used to predict erosion rates. The USLE (Universal Soil Loss Equation) method is one of the commonly used methods. The results showed that erosion that occurred in the Pitu Riase sub-watershed was 1.8 tons/ha/year for Primary Dryland Forests, 4.97 tons/ha/year in secondary dryland forests, 85.37 tons/ha/year in mixed dryland agriculture, and 58.03 tons/ha/year in shrubs and erosion that can be tolerated is 11.99 tons/ha/year in primary dryland forests, 11.64 tons/ha/year in dryland forests secondary, 8.96 tons/ha/year in mixed dryland agriculture, and 11.35 tons /ha/year in shrubs. EHI in the Pitu Riase sub-watershed is classified as heavy on mixed dry land and scrub. The recommendations for land use in the Pitu Riase sub-watershed in Sidrap Regency for mixed dryland farming are the addition of mulch on agricultural land and the creation of a terrace to reduce erosion.